2014
DOI: 10.1209/0295-5075/107/58006
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of cooperation on interdependent networks with the Prisoner's Dilemma and Snowdrift Game

Abstract: -The world in which we are living is a huge network of networks and should be described by interdependent networks. The interdependence between networks significantly affects the evolutionary dynamics of cooperation on them. Meanwhile, due to the diversity and complexity of social and biological systems, players on different networks may not interact with each other by the same way, which should be described by multiple models in evolutionary game theory, such as the Prisoner's Dilemma and Snowdrift Game. We t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…This kind of analysis of multi and mixed games could represent a new line of research in evolutionary game theory, considering the merging of various different games as statistical fluctuations. A complementary approach to the study of mixed games is the study of games on interdependent networks [72][73][74], where two distinct structured populations interact via dependency links using different games.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of analysis of multi and mixed games could represent a new line of research in evolutionary game theory, considering the merging of various different games as statistical fluctuations. A complementary approach to the study of mixed games is the study of games on interdependent networks [72][73][74], where two distinct structured populations interact via dependency links using different games.…”
Section: Introductionmentioning
confidence: 99%
“…The probability of choosing node i is (15); the probability of choosing node j is (14). c) Connection between the feature similarity network and the external network: to add m edges with probability p3 between the feature similarity network and the external network.…”
Section: ) Initial Networkmentioning
confidence: 99%
“…In the process of network generation, the edge will be randomized to reconnection, when the network reaches a certain scale; the average path of the network is small, and the clustering coefficient is high; the network has the characteristics of a "small world"; subsequently, Newman and Watts [2] found that the defects of the WS network, random network rewiring, may lead to more independent nodes appearing; in response to this phenomenon, they used adding edges instead of randomized reconnection. Later, Barabasi and Albert [3], [4] found that nodes in a network have the power law characteristic through a large number of actual networks; then they put forward a scale-free network, which is known as the BA network; then, more and more models were proposed; Flammini [5] propose a criterion of network growth that explicitly relies on the ranking of nodes according to any prestige measure; Sun et al propose a model driven by events and interests [6]; Alireza et al validate the significance of betweenness centrality in the evolution of research collaboration networks [7]; Barrat et al study the complex weighted network [8], [9]; Sun et al propose a topological evolution to simulate social activities [10]; Song et al build up a class of edge-growing network models and provide an algorithm for finding spanning trees of edge-growing network models [11]; Huang et al use spanning trees and other graphs to illustrate some results and phenomenon and try expressing mathematically key notions from researching scale-free networks [12]; a likelihood analysis is provided about evaluation models by Wang et al [13]; Zou et al propose an evolving network model growing fast in units of module [14]; article [15] finds that with the increment of network interdependence, the evolution of cooperation is dramatically promoted on the network playing Prisoner's Dilemma, and the cooperation level of the network playing Snowdrift Game reduces correspondingly; Zhuang et al study the problem of maximizing influence diffusion in a dynamic social network [16]; Llhan et al present a framework for modeling community evolution prediction in social networks [17]. www.ijacsa.thesai.org This paper proposes an e-mail communication network named "User-Information-keyword" through network analysis of an Enron dataset and analyzes the structure and user information of an e-mail network; finally, an e-mail network evolution model based on user information is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The multilayer networks [41][42][43][44] helps us understand these phenomena to explore the impact of interdependency on the cooperation. Although evolutionary game on interdependent networks has recently received substantial scholarly attention [45,46], research mainly focuses on the study of evolutionary dynamics on networks [47][48][49][50][51][52], interdependent structured populations [53,54] and game on graph. There are two types of connection mode on networks.…”
Section: Introductionmentioning
confidence: 99%